The Hematological and Biochemical Profiles of Wonosobo Sheep Blood in Various Physiological Conditions - Sarmin Sarmin Sarmin; Pudji Astuti; Claude Mona Airin (Buletin Peternakan, 2022)
The study aimed at examining the hematological and biochemical profiles of Wonosobo sheep blood in various physiological conditions. There were 32 Wonosobo sheep in the various physiological conditions, including 17 ewe lamb of 1-2 months of age, 5 pregnant female sheep of 12-48 months of age at 3 months of pregnancy, 5 ewe of 12-48 months of age in second lactation period of 1-2 months and 5 ram of 12-48 months of age. Each of the sheep was put in individual sheepfold and given Pakchong-1 grass, dried kangkong, and concentrate. Drinking water was given ad libitum. Blood sample was drawn from jugular vein and put into tubes for blood hematological and biochemical analyses. The results of the study showed that total leukocyte and lymphocyte were high in young sheep, while neutrophils was high in pregnant female sheep (P<0.05). There was not any significant physiological impact on hemoglobin, MCV, MCH, MCHC, RDW, hematocrit, platelet, monocyte, eusinophil, and basophil (P>0.05). The highest ALP activity and Pi levels were found in the ewe lamb, while low creatinine was found in the ram (P<0.05). The parameter of the activities of SGPT, SGOT, LDH, calcium, kalium, chloride, sodium, magnesium, TIBC, UIBC, TS, globulin, albumin, total protein, BUN, creatinine, glucose, cholesterol, triglyceride, HDL and LDL was not affected by physiological conditions (P>0.05). It was concluded that the impact of the physiological conditions of the Wonosobo sheep caused high total leukocyte and lymphocyte in ewe lamb and high neutrophil in pregnant female sheep, the increase in the Pi level and ALP activity of the ewe lamb, and high creatinine in the ram